Impact of cartilage graft size on success of tympanoplasty - Abdelhameed,Waleed (2017)
Abstract Introduction: In the last decade, there has been an increasing use of cartilage grafts in the primary repair of tympanic membrane perforations. The major advantages of cartilage are its stiffness and its very low metabolic requirements, which make it particularly suitable for difficult conditions, such as subtotal perforations, adhesive otitis and reoperation. Objective: To analyze the impact of different perforation sizes requiring different sizes of cartilage on the anatomical and functional outcome after tympanoplasty. Methods: Through this prospective non-controlled, non-randomized study, 50 patients underwent cartilage type 1 tympanoplasty (20 females and 30 males), with a mean age of 19.3 ± 9.8 years. According to size of perforation, patients were subdivided into three groups, Group I had perforation >50% of tympanic membrane area, in Group II patients the perforations were 25-50% of tympanic membrane area, and in Group III the perforations were ≤25% of tympanic membrane. All patients had pre and postoperative Pure Tone Average and Air Bone Gap frequencies (0.5, 1, 2, 4 kHz). All patients were followed up at least 12 months after operation. Results: The anatomical success rate among all patients was 92%, all groups showed statistical significant improvement between pre and postoperative air bone gap, no significant correlation between size of cartilage graft and degree of air bone gap improvement was noticed among the three groups. Conclusion: Size of a cartilage graft has no impact on degree of hearing improvement or anatomical success rate after tympanoplasty.